The Effect Decontamination of Sodium Hypochlorite 0.5% on shear strength buccal tube orthodontic - Muhamat Muhtar S. Abdurrohman; Budi Suhartono; Grahita Aditya; Arbono Arbono; Christina Mahardika (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: The use of fixed orthodontics has a risk of increasing plaque retention, especially the gingival margin area. The decontamination material commonly used is sodium hypochlorite 0.5%, but this antibacterial agent requires further research on the shear strength of the buccal tube attachment. The purpose of this study was to determine the effect of 0.5% sodium hypochlorite on the shear strength of buccal tube attachment after decontamination Method: The research design used was the post test only control group design. The total research sample amounted to 52 samples and was divided into 4 groups: group I Clorhexidine 2% for 1 minute, group II Clorhexidine 2% for 5 minutes, group III 0.5% NaOCl for 1 minute and group IV NaOCl 0, 5% for 5 minutes. Post Decontamination of Buccal Tube and bonding shear strength was carried out using Universal Testing Machine. The Kruskal Wallis test was carried out to see the differences in the four groups in the shear strength of attachment and the Mann Whitney test to find out the differences between groups. Result: The shear strength of the attachment by decontamination using 2% chlorhexidine for 1 minute was higher than the other 3 groups, which was 25.3 J/mm2, the lowest shear strength was for the 0.5% sodium hypochlorite group for 5 minutes, which was 16.5 J/mm2. Kruskal Wallis test results p value 0.000 (p